2018
DOI: 10.17221/77/2017-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of housing system and age of laying hens on eggshell quality, microbial contamination, and penetration of microorganisms into eggs

Abstract: Vlčková J., Tůmová E., Ketta M., Englmaierová M., Chodová D. (2018): Effect of housing system and age of laying hens on eggshell quality, microbial contamination, and penetration of microorganisms into eggs. Czech J. Anim. Sci., 63, 51-60.Hens of the laying hybrid ISA Brown were used in the study with the objective to evaluate eggshell quality, microbial contamination of eggshells, and penetration of microorganisms into the egg content in different housing systems (enriched cage: 60 hens, 10 hens per cage, 750… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…As a consequence of more frequent veterinary interventions, Cepero and Hernándiz [53] suggest that the risk of residues of antimicrobials, anthelmintics and various anticoccidials may be higher for eggs produced in non-cage housing systems. Several studies [57,60,104,105,110,116] also confirmed this finding and found that housing technologies significantly affect the number of bacteria on the surface of eggs and the level of microbial contaminants. In the case of conventional and enriched cage systems, eggshell contamination values in terms of both total bacterial counts and Escherichia coli are significantly lower compared to eggs from alternative technologies (aviary, barn), and the highest contamination was found in the case of barn housing.…”
Section: Gast Et Al (2019) [117]mentioning
confidence: 63%
See 1 more Smart Citation
“…As a consequence of more frequent veterinary interventions, Cepero and Hernándiz [53] suggest that the risk of residues of antimicrobials, anthelmintics and various anticoccidials may be higher for eggs produced in non-cage housing systems. Several studies [57,60,104,105,110,116] also confirmed this finding and found that housing technologies significantly affect the number of bacteria on the surface of eggs and the level of microbial contaminants. In the case of conventional and enriched cage systems, eggshell contamination values in terms of both total bacterial counts and Escherichia coli are significantly lower compared to eggs from alternative technologies (aviary, barn), and the highest contamination was found in the case of barn housing.…”
Section: Gast Et Al (2019) [117]mentioning
confidence: 63%
“…Several researchers [53][54][55][56][57] state that the quality of table eggs is influenced by production factors such as the age of the hen, genetics, or feeding, and point out that the comparison of the quality of eggs from farms with different housing technologies should be treated with caution. Regarding different housing systems, there is no particular technology which is suitable for the production of eggs with superior quality [58], and the higher price of eggs from alternative housing does not necessarily mean a quality difference similar to that of prices [59].…”
Section: Egg Quality Issuesmentioning
confidence: 99%
“…The risk of egg contamination is related to the penetration of microorganisms from the outside environment through the natural protective egg barriers into the egg contents [13]. With the exception of endogenous contamination, the contents of freshly laid eggs usually do not show any presence of microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors influence the functional quality of the eggshell, including the strain, age of the bird, nutrition, stress, disease and the housing system (Vlčková et al, 2018). The eggshell is considered as the natural packing material for the egg content.…”
Section: Introductionmentioning
confidence: 99%